Efektivitas Sistem Pendidikan dan Pelatihan Struktural di Pemerintah Kota Kupang - Christo Vorando Amalo (Jurnal Inovasi Kebijakan, 2017)
To carry out government duties, employees need to follow the leadership training. However, the implementation is less effective. Such as the recruitment does not match the rules and the training program impact is less significant. The purpose of this research is to measure the effectivenes of training program system and to collect data and information needed affecting to the factor of effectiveness in the program. The sampling technique is a purposive sampling and is located at the agency of Kupang City Government. The research method used is qualitative approach and the type of this research is case study. The result shows that the effectiveness on the approach varies depend on the characteristics of employee, leadership style and work climate. In the system approach, the effectiveness also varies. This is due to local political factors, like and dislike, collusion and nepotisen. The ineffectiveness of the strategic constituency approach is caused by constituency expectation to post – traning employess, fair treatment and local politics.